Meminimalkan Kesulitan Belajar Matematika Dengan Pendekatan Konstruktivis - Anita Pardede (JURNAL GLOBAL EDUKASI, 2021)
Abstract: This study aims to minimize the students' learning difficulties in math. This research was conducted in three cycles, while learning approach in this study using a constructivist approach through Student Activity Sheet (LKS) that researchers make in structured so that students can build their own knowledge by completing the worksheets in groups. Research obtained a description, students gain ≥ 67.55 on silus I by 10 students (40%), the second cycle of 16 students (67.5%) and the third cycle of 20 students (85%). From the observations obtained a description of the increased activity of students in learning that the first cycle of 6 students (42.5%), the second cycle of 17 students (65%) and the third cycle of 20 students (85%). The results of the questionnaire about students' learning respoons obtained a description of the second cycle by 11 students (47.5%), the second cycle of 17 students (72.5%) and the third cycle by 21 students (87.5%). Keywords: constructivist approach; equation of a straight line Abstrak: Penelitian ini bertujuan untuk meminimalkan kesulitan belajar siswa dalam pelajaran matematika. Penelitian ini dilaksanakan dalam tiga siklus, sedangkan pendekatan pembelajaran dalam penelitian ini menggunakan pendekatan konstruktivis melalui Lembar Kegiatan Siswa (LKS) yang peneliti buat secara berstruktur sehingga siswa bisa membangun pengetahuannya sendiri dengan jalan menyelesaikan LKS secara berkelompok. Penelitian diperoleh gambaran, siswa memperoleh ≥ 67,55 pada silus I sebesar 10 siswa (40%), siklus II sebesar 16 siswa (67,5%) dan siklus III sebesar 20 siswa (85%). Dari hasil observasi diperoleh gambaran adanya peningkatan aktivitas siswa dalam pembelajaran yaitu pada siklus I sebesar 6 siswa (42,5%), siklus II sebesar 17 siswa (65 %) dan siklus III sebesar 20 siswa (85%). Adapun hasil dari angket tentang respoons siswa terhadap pembelajaran diperoleh gambaran pada siklus I I sebesar 11 siswa (47,5 %), siklus II sebesar 17 siswa (72,5%) dan siklus III sebesar 21 siswa (87,5%). Kata kunci: pendekatan konstruktivis; persamaan garis lurus